Extended Spectrum Beta Lactamase (ESBL) Producing Klebsiella pneumoniae , a therapeutic challenge. - Chaudhary, Raina; Bhatt, Sabita Bhatt; Piya, Eva (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Klebsiella pneumoniae is one of the most common Gram negative bacteria encountered byclinicians worldwide as a cause of infections in human. Most of the infections are acquired in hospital settingtherefore, it is reported to be the amongst the 10 most common nosocomial pathogen in various studies. Nowadays,Klebsiella pneumoniae infections are complicated by increase in Extended Spectrum Beta Lactamase (ESBL)producing isolates. Therefore, this study is being conducted with the objective to fi nd out the prevalence ofESBL producing Klebsiella pneumoniaein various clinical samples and to fi nd out there sensitivity pattern. Methods: A total of 100 Klebsiella pneumoniae were isolated from various samples during the period of April2013 to November 2013 in Microbiology Unit of Shree Birendra Hospital. All the isolates were identifi ed withtheir sensitivity pattern according to standard methodology. Combination disc diffusion method was followedfor identifi cation of ESBL. Results: Out of total 100 isolates of Klebsiella pneumoniae21% were ESBL producer.ESBL producer isolatesshowed 100% sensitivity to Imepenem followed by Amikacin 57.1% and Chloramphenicol 47.6%. All theESBL isolates were resistant to both Cefotaxime and Ceftazidime. Conclusions: ESBL producer Klebsiella pneumoniae isolates were multidrug resistant. Continuous surveillanceand timely intervention with discouraging the use of cephalosporin group of antibiotics is mandatory. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12996